Políticas para a competência informacional nas bibliotecas universitárias da UFMG nos períodos de 2011 a 2016: implicações para a formação discente - Carmen Lucia de Carvalho Ramos (2017)
The objective of this research was to investigate how the actions of promoting informational competence are promoted to the students of the Academic Units of the Federal University of Minas Gerais (UFMG), promoted and implemented by the UFMG Library System (SB-UFMG). It is a qualitative approach research, that involved quantitative data, with SB-UFMG as its object, which is composed of 26 libraries, and the BU (University Library) is a Supplementary Body linked to the Rectory and is technically responsible for the provision of information Necessary for the activities of Teaching, Research and Extension of the University, as well as for the technical coordination, administration and dissemination of the information resources of the others 25 libraries of the System. The methodology adopted was characterized by bibliographical research and documentary research of all libraries of the SB-UFMG verifying the physical and digital documents relevant to the research. Faced with the documentation of the collected documentary mass, it was decided to work on the SB / UFMG Annual Reports with regard to the training of users in order to promote their informational competence. It was concluded that there is an implicit policy, in this sense, perceived in the way the actions are given for the training of users. In order to contribute to the promotion of informational competence of SB / UFMG users, as a result of this research, a training course was developed for information users for informational competence to be applied as a pilot project in the Library Professora Alaíde Lisboa de Oliveira of the Faculty of Education with proposals of effective formation of students linked to the UFMG, in the context of an information policy within SB / UFMG, with the intention of developing their informational competence, in a bet that this competence will bring positive impacts in personal and professional life of the graduated student from the UFMG.